Synthesis of Some New 5[[(substituted amino)methylbenzimidazole-2-yl]- methyl-N-[(substituted-phenyl)methylene]-1,3,4-Thiadiazoles-2-amino as Potential Anthelmintic Drugs - Fadayan, Manouchehr; Pakdaman, A.S.H.; Kulkarni, Y.D. (Asian Journal of Chemistry, 2010)
The title compounds have been synthesised and screened for their anthelmintic activity against Hymenolepsis nana infection in mice and Nippostrongylus brasiliensis infection in rats. These compounds have also been tested for their in vivo and in vitro activity against tobacco mosaic virus (TMV) and cucumber green mottel mosaic virus (CGMMV).